2017
DOI: 10.1097/paf.0000000000000287
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Hydrostatic Test

Abstract: The hydrostatic test is used to help determine if there has been a live birth. Computed tomography (CT), with its ability to detect and localize air/gas in the body, offers a rapid, noninvasive tool for assessment.Four baby deaths (20 to 25 weeks' gestation) in which the hydrostatic test, radiographs, and CT were performed before autopsy are presented. In 2 cases, considered stillbirths, the lungs and liver sank, and there was no air seen in the lungs or gas in the liver on CT. Histology of the lungs showed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, performance of the lung float test alone can lead to erroneous conclusions 34 . We therefore used the liver as a control for air produced by decomposition 32 . When combined with a careful evaluation of the lung morphology, stomach contents and brown adipose tissue, a reliable predictor of post-partum viability may be obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, performance of the lung float test alone can lead to erroneous conclusions 34 . We therefore used the liver as a control for air produced by decomposition 32 . When combined with a careful evaluation of the lung morphology, stomach contents and brown adipose tissue, a reliable predictor of post-partum viability may be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Lung morphology was evaluated for degree of inflatedness, colouration and aeration. A lung float test was performed by removing a fragment of a lung lobe and a same size fragment of liver (as control for decomposition 32, 38 ) and putting both inside an Eppendorf tube filled with water. Whether the fragments sank or floated was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, the implementation of PMCT imaging has been used to detect the presence of gas in the infant. It is superior to plain radiographs in determining the distribution pattern of air in the lungs, gastrointestinal tract, and liver and has been shown to have good agreement with the lung flotation test (20, 27, 32). Gas in the stomach and upper gastrointestinal tract along with uniform gas distribution within the lungs on three-dimensional reconstruction of PMCT provides convincing evidence that a neonate has breathed naturally prior to demise and was, therefore, live born (20).…”
Section: Discussionmentioning
confidence: 99%
“…The test is based on the premise that if an infant has breathed then the lungs will be inflated. Hence, if the lungs float when placed in water, this indicates that they are inflated and the infant had breathed and was Over time there have been innumerable variations to the procedure for performing the lung flotation test (25) including: variations in the temperature of the water used for flotation; flotation of the entire thoracic block, individual lungs, individual lung lobes, and/or pieces of lung; flotation of a piece of liver to assess for gaseous decomposition, where if the liver floats, the lung flotation test is considered inconclusive (27); flotation of the stomach and intestines to demonstrate air in the gastrointestinal tract attributed to swallowing, though it has since been recognized that air in the gastrointestinal tract can also be artefactual due to resuscitation or gaseous decomposition (6,7,28); and ligation of airways and/or pulmonary vessels prior to flotation (19,20,25,26).…”
Section: Lung Flotation Testmentioning
confidence: 99%
“…Postmortem CT can be used for skeletal and lung assessment in fetal/neonatal death, but Arthurs et al [41] have found that because of poor soft-tissue contrast CT is less reliable than MRI, particularly in fetuses, unless specific skeletal evaluation is required. Postmortem CT has been used to identify small amounts of air in the airway and lungs in a neonate to help determine whether the child was alive at birth versus being stillborn [26,45] (Fig. 1); however, radiographs or MRI [46] could be utilized for this purpose, as well.…”
Section: Clinical Applications Of Postmortem Ctmentioning
confidence: 99%